2010
DOI: 10.1016/j.foodcont.2009.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes in raw salad vegetables sold at retail level in Malaysia

Abstract: a b s t r a c tA range of commercially available vegetables (n = 306) that are consumed in the minimally processed state in Malaysia was examined for the presence of Listeria spp. and Listeria monocytogenes to provide information on the occurrence of such organisms in these vegetables. Analysis was carried out using the most probable number-polymerase chain reaction (MPN-PCR) method. It was found that Listeria spp. and L. monocytogenes could be detected in 33.3% and 22.5% of the vegetables respectively. L. mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 21 publications
3
60
2
2
Order By: Relevance
“…On the other hand, L. monocytogenes has been barely linked to foodborne disease outbreaks in which vegetables are the foods implicated (Harris et al, 2003), but it has been constantly isolated from vegetables (Cordano & Jacquet, 2009;Little et al, 2007;Oliveira, Ribeiro et al, 2010;Ponniah et al, 2010). Therefore, the evaluation of the presence of these microorganisms in MPV is of great relevance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, L. monocytogenes has been barely linked to foodborne disease outbreaks in which vegetables are the foods implicated (Harris et al, 2003), but it has been constantly isolated from vegetables (Cordano & Jacquet, 2009;Little et al, 2007;Oliveira, Ribeiro et al, 2010;Ponniah et al, 2010). Therefore, the evaluation of the presence of these microorganisms in MPV is of great relevance.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported on the occurrence of foodborne pathogens in vegetables, particularly in MPV, such as Salmonella spp. (Bhagwat, 2004;Bohaychuk et al, 2009;Elviss et al, 2009;Islam et al, 2004;Khoo et al, 2009;Salleh et al, 2003;Sant'Ana, Landgraf, Destro, & Franco, 2011), pathogenic Escherichia coli (Balagué et al, 2006), and Listeria monocytogenes (Aguado, Vitas, & García-Jalón, 2004;Cordano & Jacquet, 2009;Little et al, 2007;Oliveira, Ribeiro, Bergamini, & Martinis, 2010;Ponniah et al, 2010;Vitas & Garcia-Jalon, 2004). Studies have also been focused on the MPV shelf-life and hygiene indicators microorganisms, such as mesophilic and psychrotrophic microorganisms, Pseudomonas spp., coliforms, and E. coli (Abadias, Usall, Anguera, Solsona, & Viñas, 2008;Fröder et al, 2007;Ilic, Odomeru, & LeJeune, 2008;Meldrum et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Further, presence of Listeria spp. in vegetables, such as cabbage, lettuce, tomato, watermelon, oranges have been reported in many countries, including Sri Lanka (Gunasena et al 1995;Caggia et al 2009;Ponniah et al 2010). Further, WHO reports that leafy green vegetables are of great concern in terms of microbiological hazards (WHO, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although listeriosis infections are rare, the fatality rate is as high as 20%e30% annually (Allerberger, 2003;Yucel et al, 2005). To date, there are no documented listeriosis infection cases in Malaysia (Hassan, Endang, Son, Raha, & Gulam, 2001;Ponniah et al, 2010); however, without safeguards, such infections may occur. Protective measures, such as the development of a surveillance and detection system concerning food safety, are fundamental to ensure that raw and processed foods derived from fish, chicken and meats are safe for human consumption.…”
Section: Introductionmentioning
confidence: 99%